2013
DOI: 10.1096/fj.12-223057
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ligands for the NKG2D receptor are released during HIV‐1 infection and impair NKG2D expression and cytotoxicity of NK cells

Abstract: In humans, the interaction of the natural killer group 2 member D (NKG2D)-activating receptor on natural killer (NK) and CD8(+) T cells with its major histocompatibility complex class I-related chain (MIC) and UL16 binding protein (ULBP) ligands (NKG2DLs) promotes recognition and elimination of stressed cells, such as tumor or infected cells. Here, we investigated the capacity of HIV-1 to modulate NKG2DL expression and escape NGK2D-mediated immunosurveillance. In CD4(+) T lymphocytes, both cell surface express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 46 publications
4
82
0
3
Order By: Relevance
“…Intracellular BAT3 can be released in exosomes by DC and bind to NKp30, thereby triggering NK cell functions (26). Similarly, NKG2D ligands including ULBP molecules are shed in response to HIV-1 and inhibit NKG2D-mediated NK cell activation (27). Further investigation of the expression of such soluble ligands of NK cell-activating receptors during LASV infection would be informative.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular BAT3 can be released in exosomes by DC and bind to NKp30, thereby triggering NK cell functions (26). Similarly, NKG2D ligands including ULBP molecules are shed in response to HIV-1 and inhibit NKG2D-mediated NK cell activation (27). Further investigation of the expression of such soluble ligands of NK cell-activating receptors during LASV infection would be informative.…”
Section: Discussionmentioning
confidence: 99%
“…CD62L downmodulation on HIV-1-infected T cells could be due to increased protein shedding by MMPs, a family of enzymes activated during HIV-1 infection through poorly understood mechanisms (29). To address this point, we measured by ELISA the amounts of sCD62L accumulating in the medium of primary CD4 ϩ T lymphocytes infected or not with HIV-1 and cultivated with a broad-spectrum MMPI (25 M) or equivalent amounts of DMSO solvent, a procedure that we previously set up (30). In control cultures (DMSO), noninfected and HIV-infected cells released amounts of sCD62L that were comparable and ϳ2-fold higher than that of nonactivated cells, indicating that CD62L shedding induced by T cell activation occurs independently of HIV-1 (Fig.…”
Section: Hiv-1 Infection Induces Cd62l Downregulation In Cd4mentioning
confidence: 99%
“…For each target, forward (F) and reverse (R) primers were designed across exons to avoid amplification of genomic DNA, as validated in pilot assays: CD62L(F), 5=-CAGCCCTCTGTTACACAGCTT-3=; CD62L(R), 5=-GCCCATAGTACCCCACATCA-3=; G6PDH(F), 5=-ATC GACCACTACCTGGGCAA-3=; and G6PDH(R), 5=-TTCTGCATCACG TCCCGGA-3=. The number of cycles (30) was set to the exponential phase of the PCR in order to allow semiquantitative comparisons among samples.…”
mentioning
confidence: 99%
“…Therefore, it is possible that this behavior is due to the partial immune recovery of HAART during the early years of treatment, even in cancer conditions. Previous studies have shown that HAART modulates the NKG2D receptor expression among individuals infected with HIV-1 [24][25]. However, there are few studies that have set out to examine the NKG2D expression in NK cells in chronically infected patients [23].…”
Section: Discussionmentioning
confidence: 99%